Media and Information Literacy Upskilling for Educators at Universities: Ukrainian Context - Babushko, Svitlana; Solovei, Myroslav; Solovei, Liudmyla (Educological discourse, 2023)
Currently, media and information literacy (MIL) has gained considerable significance worldwide and, particularly, in Ukraine. The efficient way to develop the MIL skills of the citizens is through well-trained educators as they help navigate in information and cyberspace. Unfortunately, the issue of MIL upskilling of university educators is paid little attention to. Hence, the researchers addressed the question to clarify the situation. A qualitative research methodology was applied to find out the current state of the MIL level of university educators and their need for special MIL upskilling training. The methodology included several steps: literature review, preparation of interview questions, observation and communication, interaction in the professional groups of university educators, conducting semi-structured interviews, data analysis, and working out a set of recommendations. There are several terms that Ukrainian university educators use with the meaning of “media and information literacy” varying from “media education”, and “media competency” to “media training”. Besides, there are different interpretations of the term and different characteristics of a media-literate person. The interviews demonstrated that the level of MIL among most university educators is not sufficient, in their opinion. They realize the benefits of being a media literate person both for personal and professional development. And as a result, most of them are using MIL resources within non-formal and informal education systems. There are appropriate resources in the Ukrainian language to develop or master MIL skills. However, they are mostly for school teachers. Scarce resources are designed for university educators to upskill their MIL. Thus, the conclusion was made on the urgent necessity of Ukrainian university educators in providing special MIL training and in designing corresponding methodical resources. A set of recommendations on three levels (national, institutional, and personal) was offered to satisfy the demand.